Collaboration and involvement of persons with lived experience in planning Canada's At Home/Chez Soi project. (17th February 2015) - Nelson, Geoffrey; Macnaughton, Eric; Curwood, Susan Eckerle; Egalité, Nathalie; Voronka, Jijian; Fleury, Marie‐Josée; Kirst, Maritt; Flowers, Linsay; Patterson, Michelle; Dudley, Michael; Piat, Myra; Goering, Paula
Abstract: Planning the implementation of evidence‐based mental health services entails commitment to both rigour and community relevance, which entails navigating the challenges of collaboration between professionals and community members in a planning environment which is neither 'top‐down' nor 'bottom‐up'. This research focused on collaboration among different stakeholders (e.g. researchers, service‐providers, persons with lived experience [PWLE]) at five project sites across Canada in the planning of At Home/Chez Soi, a Housing First initiative for homeless people with mental health problems. The research addressed the question of what strategies worked well or less well in achieving successful collaboration, given the opportunities and challenges within this complex 'hybrid' planning environment. Using qualitative methods, 131 local stakeholders participated in key informant or focus group interviews between October 2009 and February 2010. Site researchers identified themes in the data, using the constant comparative method. Strategies that enhanced collaboration included the development of a common vision, values and purpose around the Housing First approach, developing a sense of belonging and commitment among stakeholders, bridging strategies employed by Site Co‐ordinators and multiple strategies to engage PWLE. At the same time, a tight timeline, initial tensions, questions and resistance regarding project and research parameters, and lack of experience in engaging PWLE challenged collaboration. In a hybrid planning environment, clear communication and specific strategies are required that flow from an understanding that the process is neither fully participatory nor expert‐driven, but rather a hybrid of both.